Pengaruh Sistem Informasi Akademik (SIKAD) dan Kualitas Pelayanan Terhadap Kepuasan Mahasiswa Pada Universitas Islam Riau - Yul Efnita; Syaefulloh; Suci Widana (STEKOM PRESS, 2021)
This reaserch was conducted at the Islamic University of Riau in the city Pekanbaru, researchers wanted to see how the level of student satisfaction with the academic information system (SIKAD) and the quality of services provided by the Islamic University of Riau on student satisfaction, especially in the 2018/2019 class, sample size was taken with slovin obtained 394 students from a total population of 27,733 students, while the respondents were 165 students who responded to the questionnaire from the google form, via student email. Along with the current COVID-19 pandemic which has occurred for more than a year until the time this research is conducted in 2021. The analytical tool used in the study is Smart PLS. 3, with evaluation of measurement model and evaluation of structural model. Based on this analysis, it was found that the academic information system (SIKAD) and service quality had an effect on student satisfaction of 93.1%. The test for the feasibility of the model used with the Normed Fit Index (NFI) of 0.841 means that the model that is owned is fit, is in the marginal fit category because it is at a critical value of 0.8 NFI 0.90. Path coefficients to see the magnitude of the effect of exogenous variables on endogenous variables, with the t-statistics method (bootstrapping) both variables have a positive and significant effect.